HISTORY EDUCATION MODEL DEVELOPMENT FOR THE 21ST CENTURY - Kamarga, Hansiswany (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2013)
This research aims to obtain a form of the 21st Century History EducationModel based on the four converging forces, namely knowledge work, thinking tools,digital lifestyles, and learning research through local history as the substance in the ICT in History Learning course. It is done to anticipate the need of skill development that demanded in the 21st century, especially for Department of History Education which will produce the history teachers. The results of this research can be used and developed by the Department of History Education as the education model in every course which discusses about the historical thinking development. The results of the21st Century History Education Model show that (a) in knowledge work aspect, 90,3% of students opined that this course gave them much knowledge about the developmentin information and argued technology world; (b) in thinking tools, this course got good enough’ mark to help the students in learning, working, and recreating through browsers, email, blogs, UPI SPOT (Sistem Pembelajaran Online Terpadu / Integrated Online Instructional System, accessed on spot.upi.edu), and Wi-Fi facility in the faculty; (c) in digital lifestyles aspect, ICT in History Learning course could bring the changing of students’ lifestyle and habit. The students started to habitually do their task by them selves or by groups without being bordered by time or space. The last aspect, (d) learning research aspect of the students are good enough in understanding in searching and developing the information of local history substance via internet, but in developing their skill of updating the knowledge into a meaningful learning, and skill of confirming the information of local history substance that been got from the internet and the local region through observation and interview, 60% of students did feel difficult. Developing students skills in researching, searching, and finding their region potencies through the tasks which related to their locality also could grow their pride with their locality itself, and their appreciation between the other regions’ diversity. Kind of those thoughts are the requirement of the people in the 21st century: always think like a researcher search and find something new.